Cold War Books: George Minden and His Field Workers, 1973–1990. Issue 1 (February 2020) - Sowiński, Paweł
The article deals with the history of the so-called Book Program—a joint effort of the US government, the East European diaspora, and readers of books prohibited behind the Iron Curtain. This was one of the most brilliant smuggling operations in the history of Eastern Europe. In 1956– 1989, the operational budget was used for the purchase and delivery to the population of Soviet-dominated Europe of about ten million publications in an effort to undermine communist rule there. This study adds new things to what is already known about the cultural Cold War. Concentrating mostly on Polish cases, the author examines relations between state and non-state actors inside the network of the book program. Using historical materials, he captures the complexity of the grassroots activists–US government interactions, which were finally successful, but this communication also proved difficult for both parties. Contributing to the discussion of hegemony and autonomy in state–private networks, the author points out cooperation and negotiation, not the co-optation of diaspora communities by the US government.